Case Report: Nuchal Bursitis Associated With Borrelia burgdorferi Infection in a Horse - Guarino, Cassandra; Pinn-Woodcock, Toby; Levine, David G.; Miller, Julia; Johnson, Amy L. (Frontiers in Veterinary Science, 2021)
Cases of cranial nuchal bursitis associated with Borrelia burgdorferi infection have not been thoroughly described. Here, we describe the case of a 17-year-old mare that was presented for low head carriage, dull demeanor, and resistance to haltering. Imaging supported a diagnosis of nuchal bursitis, and bursoscopy with surgical debridement of the nuchal bursa was performed. B. burgdorferi was identified by molecular diagnostics in serial samples of the bursal fluid, with no other organisms identified. Serology revealed significant elevation in antibodies directed against OspA of B. burgdorferi, but not the typical infection markers, OspC and OspF. IV ceftiofur was administered for 80 days, and the nuchal bursa was directly injected with ceftiofur. The mare recovered and was able to return to work with no recrudescence of clinical signs over the following year to date. Infection with B. burgdorferi should be considered as a differential in cases of septic nuchal bursitis.